Pengaruh Green Marketing Dan Corporate Social Responsibility Terhadap Brand Image Pada Produk Makanan Cepat Saji KFC Cabang Sutomo Di Kota Medan - Lasma Lenida Rosinta Sianipar; Dame Ria Rananta Saragi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This research was conducted to determine the effect of green marketing and corporate social responsibility on brand image at the KFC fast food restaurant in Medan City. The population in this study were consumers at KFC fast food restaurants in Medan City. This research uses non probability sampling technique. Data was collected by distributing questionnaires, the number of responses in this study were 100 respondents. The hypothesis is tested using path analysis techniques / path coefficient. The results of hypothesis testing show that all the proposed hypotheses are accepted. Green marketing has a positive and significant effect on brand image, corporate social responsibility has a positive and significant effect on brand image, and green marketing has a positive and significant effect on brand image through corporate social responsibility as the mediation. This is in line with research conducted by Santoso and Ardani (2017)